Assessing the benefits of installing energy storage in a household equipped with photovoltaic panels - Klumpner, Christian; El Boudali, Alaa (2015)
This paper evaluates the technical and financial impact of installing energy storage in a house equipped with Photovoltaic (PV) panels subject to the Feed-In Tariff (FIT). An additional benefit of installing energy storage is the possibility to purchase electricity off-peak (overnight) at a cheap rate and replace consumption during day/peak time and for this reason, the Economy7 tariff is considered. The studies carried out are using real data of PV generation and household consumption continuously recorded over a week for each of the four seasons, from a UK installation. A functional model of the battery system is implemented that includes voltage dependency versus state of charge and maximum charging and discharging currents, that account for the limitations of the amount of charge - size dependant and current that can reflect the power capability of the battery to preserve high conversion efficiencies and lifetime. As initial investigations point to a rather large battery system to maximize the synergy between PV and energy storage, the paper investigates how the performance indicators vary with the battery size. It is found that there may be a critical battery size up to which the peak rate consumption and the PV energy export decrease more rapidly. Above this critical point which in this study lies at around 25-30% of the battery size that would allow full local use of PV energy generated, the impact of increasing the battery size reduces, therefore the return of investment as a percentage decreases.